PERLINDUNGAN HUKUM TERHADAP PERUSAHAAN PASANGAN USAHA YANG BERITIKAD BAIK DALAM PERJANJIAN MODAL VENTURA - Rudyanti Dorotea Tobing (Jurnal Ilmu Hukum Tambun Bungai, 2016)
Formation of Venture Capital Company (PMV) in Indonesia is to finance to SMEs as Partnership Company (PPU). The main function of PMV is equity (equity participation) to the PPU, especially entrepreneurs beginners. Article 1 paragraph 2 of Regulation of the Minister of Finance No. 18 / PMK.010 / 2012 on the Venture Capital Company states that: "Venture Capital is a business entity that conducts business financing / equity into a company (investee company) for a certain period in the form of shares of stock, participation in the form of the purchase of convertible bonds and / or financing based on the division in the results. " In practice, the majority of PMV is engaged in the provision of credit and direct loans like banks. This situation triggered by the increasing number of business people who need loans for their business. On the other hand there are still many businesses that do not understand the true nature of venture capital firms. In ignorance and in desperate conditions, many businesses are doing the borrowing agreement with PMV. Arrangements were made just like a bank loan agreement following the security agreement in the form of imposition of Hak Tanggungan. When the PPU of default, the mortgage was executed and auctioned. PMV do into agreement for the understanding the true state of the PPU were in desperate need of funds. Article 1338 paragraph (3) of the Civil Code states that the agreement must be implemented in good faith. Good faith should be available from the moment the process of negotiating and drafting of contracts and the implementation of the contract. In essence the PPU has to implement its obligations in good faith, but instead PMV which does not apply the principle of good faith. PPU good faith should get legal protection. As a form of legal protection against PPU good faith, there should be strict sanctions to PMV who do venture capital agreement that does not comply with the legislation.